AN ANALYSIS OF DIRECTIVE SPEECH ACT IN “PUSS IN BOOTS : THE LAST WISH” MOVIE - Syahcorina, Oscar Dela; Delfi, Syofia; Erni, Erni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This research aims to find out the types of Directive Speech Acts bythe main characters “Puss in